Metabolic Syndrome in Chronic Obstructive Pulmonary Disease (COPD) Patients and Its Association with Severity of COPD: A Study from Chhattisgarh, India - Dr. Jyoti Banjare; Dr. Jyoti Banjare; Dr. Archana Toppo; Dr. Yogendra Malhotra; Dr. Ajit Kumar; Dr. D.P. Lakra; Dr. Prachi Dubey (International Journal of Pharma and Bio Sciences, 2023)
Metabolic Syndrome is found to be more frequent in chronic obstructive pulmonary disease (COPD) as it seems to be related to systemic inflammation. Chronic Obstructive Pulmonary Disease (COPD) is a growing cause of morbidity and mortality worldwide and will become one of the leading causes of death in near future. This study aims to detect metabolic syndrome in COPD patients and its association with the severity of COPD. The current study was Hospital based cross-sectional observational study. 60 Stable COPD patients were included. Patient of Chronic Obstructive Pulmonary Disease attending general medicine OPD, casualty, admitted to Dr. BRAM Hospital, Raipur (India) medicine ward. After obtaining informed written consent from participants, demographic details, and chief complaints, a Pulmonary Function Test for clinically suspected cases of COPD was obtained. Clinical examinations, including waist circumference, were observed. Blood investigations were done. Staging of COPD was done using GOLD criteria. The association of the severity of COPD with Metabolic Syndrome was then done using statistical tools. There is no statistically significant difference between the prevalence of Metabolic Syndrome in different COPD stages (P=0.199). There is also a significant difference in pre-FEV1 (P=0.015) and post-FEV1 (P=0.03) values in patients with and without Metabolic Syndrome. At the end of the study, it can be concluded that waist circumference (P=0.007) significantly differs in patients with and without metabolic syndrome. At the same time, other variables like weight, height, BMI, and waist-hip ratio do not show any significant difference.